Zum Fraßvermögen der Blattkäfer Diabrotica balteata Lec., Andrector ruficornis (Oliv.) und Systena basalis Duval. sowie der Minierfliege Liriomyza trifolii (Burgess) an der Bohne (Phaseolus vulgaris L.). - Heyer, Wolfgang; Chiang Lok, Maria Luisa; Cruz, Bienvenido (Contributions to Entomology = Beiträge zur Entomologie, 1991)
The damage capacity of the leaf beetles Diabrotica balteata Lec., Andrector ruficornis (Oliv.) and Systena basalis Duval. was studied under model conditions (glastubes) and that of Liriomyza trifolii (Burgess) larvae by evaluating bean leaves collected in the field. Considering development time and duration of presence of these dangerous insects in bean crops the damage per individuum was assessed to reach 70 cm² (D. balteata), 46 cm² (A. ruficornis), 4 cm² (S. basalis) and 0,8 cm² (L. trifolii).